Simulation of Single Phase 3-level Z-source NPC Inverter with PV System - R. Palanisamy; K. Selvakumar; D. Selvabharathi; D. Karthikeyan; Udayan Nayak; Sahil Walia; Pratik Chawda (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This paper elucidates simulation of single phase 3-level z-source neutral point clamped (NPC) inverter with PV system. single phase NPC inverter employed due to its advantages like less voltage stress, reduced harmonic content, minimsed CMV and voltage stress is low. Z-source network is engaged to boost input voltage getting from the photovoltaic system, which is manoeuvre in shoot through and non-shoot through conditions. This proposed scheme utilized to enhance the output voltage, minimise THD and the leakage current can be avoided with help of split inductor connected with output of inverter system. sinusiodal pulse width modulation (SPWM) used as control technique for the proposed 3-level z-source NPC inverter. The simulation results of this scheme has been verified using matlab/simulink.